Cultural Views on Physical Disabilities Before and After Fulfilling Accessibility - NURMIATI, Dwi Rahayu; HAPSARI, Nurliana Cipta; TAFTAZAN, Budi Muhammad (PT Batara Swastika Harati, 2025)
Yakkum Emergency Unit (YEU) is a non-governmental organization that focuses on emergency disaster response. YEU also has a mandate to provide protection and provide for the needs of vulnerable groups, including people with physical disabilities. One of the programs designed is to provide household level accessibility for people with physical disabilities. This includes providing emergency lights, installing handrails, making ramps, and repairing bathrooms. The purpose of this research is to identify cultural views towards physical disability before and after compliance with accessibility. This shows a comparison of society's views towards physical disability before and after the action including accessibility by the YAKKUM Emergency Unit which includes an evaluation of how stigma, perception and handling of individuals are carried out. physical disabilities change or do not change over time. This research uses qualitative methods. Qualitative research is suitable for cultural research because it uses data collection techniques such as data reduction and drawing conclusions. Previously, society had a stigma or negative perception towards individuals with physical disabilities, but after this intervention, there was an increase in social acceptance and inclusion for them. The role of the YAKKUM Emergency Unit in meeting accessibility needs in Ciputri Village is very important. Concrete steps such as building accessibility infrastructure have a real impact on the quality of life for individuals with physical disabilities in the community.